Presence of Africa in African-American Literature - Dhakal, Lekha Nath (KMC Research Journal, 2017)
African traditions and rituals survived the antagonistic forces which transported them from their ancestral lands to other continents is an established fact in world history. However, how they have been employed in varied artistic forms still requires further investigation. The traditions and rituals still practiced by the people of African diaspora in various parts of the globe are connected to Africa. These primitive traditions stored both orally and in written form are abundantly found in African-American literature.